Aromatherapy with inhalation effectively alleviates the test anxiety of college students: A meta-analysis - Luan, Jiage; Yang, Mengshu; Zhao, Yan; Zang, Yu; Zhang, Ziyu; Chen, Haiying (Frontiers in Psychology, 2023)
Objective: Test anxiety is one of the common psychological and behavioural problems of college students, which can result in poor academic performance and even academic failure. Aromatherapy has been proposed as a promising method to reduce test anxiety in college students, but its precise efficacy has not been fully confirmed. This meta-analysis evaluated the effects of aromatherapy on the symptoms of test anxiety in college students to serve as a reference for future research and provide more scientific and exact evidence. Methods: PubMed, The Cochrane Library, Web of Science, Embase, CINAHL, Science Direct, CNKI, VIP, and Wanfang Data were electronically searched from inception to June 2022 to identify randomized controlled trials on aromatherapy for treating students’ test anxiety. The Cochrane Risk of Bias Assessment Tool for randomized controlled trials (RCTs) was used by two reviewers to critically and independently assess the methodological quality of the included studies. Review Manager 5.4 was used for the meta-analysis. Stata 17.0 was used for sensitivity analysis and Egger’s test. Results: Seven RCTs included 425 patients, with a moderate risk of bias in the included studies. The meta-analysis found that aromatherapy effectively reduced test anxiety in college students (SMD = −0.67, p ＜0.01), with high heterogeneity of results (I² = 72%). The different types of essential oil devices used in the study are the source of inter-study heterogeneity. Subgroup analysis suggested that most effective methods were aromatherapy with compound essential oils (SMD = −0.91, p < 0.01), and using cloths or pads as the essential oil devices (SMD = −1.03, p < 0.01). There was no difference between aromatherapy and placebo control groups (SMD = −0.65, p = 0.25). Conclusion: Aromatherapy with inhalation can help relieve test anxiety in college students, but more and higher-quality studies are needed. This study provides a reference for future research designs in terms of the selection of essential oil types and devices and the design of research groups. Systematic Review Registration: PROSPERO, identifier: CRD42022345767.